Development, validation and evaluation of medical education e-professionalim (MEeP) framework - Salman, Shaista (2023)
One can argue that the true intention of medical education is to produce virtuous and humanistic healthcare professionals who demonstrate perseverance and professional integrity. However, today's medicine has witnessed a substantial change in the both the behaviour and performance of healthcare persons, particularly those in medical practice. Professional bodies produce guidance for good professional behaviour. However, professional demeanour and conduct have changed with digital platforms such as Social Networking Sites (SNS). Such a paradigm shift has challenged the medical professional's values, behaviours, and identities, thus blurring the distinct lines between personal and professional lives. E-professionalism, a new emerging construct, was developed to attenuate and align standard professional behaviours in the digital realm. There was, however, a gap in how to change the digital professional behaviours of healthcare professionals while working online sharing information on SNS. This led to developing my PhD proposal to produce an essential framework to curtail the escalating number of unprofessional incidents. This research aimed to develop, validate and evaluate a framework to clarify the meaning of eprofessionalism and to guide and improve behaviours while sharing on SNS. Using a pragmatic approach, I devised a sequential mixed methods approach. This multiphased research was conducted during 2019-2021 using a range of study designs, sampling techniques, data collection and analysis strategies. This included literature reviews, data curation, online surveys, e-Delphi, expert validation and educational intervention. Using the Theory of Planned Behaviour (TPB) as a theoretical underpinning, I evaluated the MEeP framework against Kirkpatrick's model with the help of a pre-post workshop design on undergraduate medical students from three different institutions. An inductive-deductive and abductive approach was used for the qualitative data analysis as per the various phases of the research. On the other hand, quantitative data was dealt with using SPSS 22 by performing descriptive and pathway analysis. Phase I part of the study, the systematic review of 44-studies showed that the concept of e-professionalism was defined but the guidance on how to behave professionally in the digital realm was absent. A multi-construct Mission-based Medical Education e-Professionalism (MEeP) framework comprising of values, behaviour and identity constructs was developed using a pluralist approach and triangulating the data from the systematic review (44 studies), survey responses (n=381) and Delphi experts (n=15) findings while implying a convergent parallel design. In Phase II, I validated the MEeP regarding content and face validity using a modified six-step approach where six experts attributed and highlighted its resemblance with the emotional intelligence paradigm. Finally, in Phase III I evaluated the MEeP framework (n=59) was evaluated using equal status QUAL_QUAN strategy. Using the methodological and data triangulation, both qualitative and quantitative findings synergistically revealed that mission improved the desired attributes in medical professionals' value, behaviour and identity domains. The newly developed MEeP framework holds great promise in fortifying the digital professional behaviours of healthcare professionals. The framework has been shown to change and guide online professional behaviours.